Transformation of Traditional Islamic Education: Dayah as a Modern Educational Institution in Post-Conflict Aceh - Erawadi, Erawadi; Setiadi, Fadlan Masykura (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2023)
This study explored the transformation of Dayah institutions in Aceh, focusing on their change from traditional religious schools to a modern Islamic educational institutions, particularly in the post-conflict era. The integration of modern education into Dayah has sparked a dynamic contestation between tradition and modernity, reflecting broader social and political changes in Aceh. This study also emphasized Dayah's resilience and continued influence on post-conflict reconciliation and contemporary religious practices in Aceh. Meanwhile, this research employed qualitative research with a type of literature review. The findings showed that the transformation of Dayah has formed an integrated educational system that combines traditional Islamic teachings with modern education, fostering the development of science and technology. The Dayah system has successfully cultivated a society with a profound, comprehensive understanding of Islam and has contributed to the cultivation of tolerant individuals by alienating students from radical thought patterns.